Ocorrência do subtipo B do vírus da imunodeficiência felina em gatos domésticos da região sul do estado do Rio Grande do Sul, Brasil - Silva, F.s.; Castro, C.c.; Finger, P.f.; Silva, D.s.; Taniwaki, S.a. [UNESP]; Ullmann, L.s. [UNESP]; Fischer, G.; Vargas, G.d.; Lima, M.; Araújo Jr, J.p. [UNESP]; Hübner, S.o. (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2014)
In Brazil there are few studies on the occurrence of the feline immunodeficiency virus (FIV) infection and its subtypes, which are essential for the development of vaccines and new diagnostic tests. The present study investigated the occurrence of the FIV infection between 2010 and 2011 in domestic cats submitted to medical attendance in the city of Pelotas and nearby area. Total blood samples of seventy cats, suspected (28) or not (42) of infection by FIV were analyzed by nested PCR in order to perform a diagnosis. The results pointed to a FIV infection frequency of 15.7% (11/70) and the analysis of the risk factors related to infection (sex, age and clinical condition) evidenced a greater occurrence in cats up to 10 years of age with chronic and recurrent infections. Eight samples found positive by nested PCR were submitted to DNA sequencing indicating that only the subtype B was detected in the studied region.

No Brasil existem poucos estudos sobre a ocorrência da infecção pelo vírus da imunodeficiência felina (FIV), assim como a determinação dos subtipos circulantes, o que é indispensável para o desenvolvimento de vacinas e novos testes diagnósticos. O presente trabalho investigou a ocorrência da infecção pelo FIV entre os anos de 2010 e 2011 em gatos domésticos submetidos a atendimento clínico na cidade de Pelotas e região. Amostras de sangue total de 70 animais, incluindo suspeitos (28) ou não suspeitos (42) da infecção pelo FIV, foram submetidas à reação de PCR nested. Os resultados indicaram uma frequência de infecção de 15,7% (11/70) e a análise dos fatores associados (sexo, idade e condição clínica) evidenciou uma maior ocorrência em gatos com idade superior a 10 anos e acometidos por infecções crônicas e recidivantes. Oito amostras positivas na PCR nested foram submetidas a sequenciamento genômico e somente o subtipo B foi detectado na região estudada.
Occurrence of subtype B of the feline immunodeficiency virus in domestic cats from the south region of Rio Grande do Sul state, Brazil
Keywords: gato; vírus da imunodeficiência felina; PCR; cat; feline immunodeficiency virus; PCR